Avaliação sistêmica dos fatores críticos de sucesso e insucesso no processo de desdobramento da estratégia - Nuncio, Rodrigo Girotto (Universidade do Vale do Rio dos Sinos, 2016)
In the current context of complex, competitive and dynamic environments, strategy is a topic widely studied in organizations and academies. However, there are few studies on deployment and implementation of the strategy itself, as well as on the effectiveness of its implementation. This study aims to investigate the main factors causing the discrepancies between the objectives arising from the strategic planning and the result at the end of the implementation of the plan, regarded as critical to the deployment process. For this investigation, this research uses the artifice of systems thinking to analyze the causal relationships between the variables found through a literature search and a field research with professionals of strategy planning and execution. At the end this paper propose an artefact to assist in mitigating the critical factors for the deployment process. As a research method, this paper uses the Design Science Research as guiding the step in conducting the research and construction of the proposed artefact. This research is, at the end, evaluated and validated by experts in the field of business strategy.
Keywords: Desdobramento estratégico; Pensamento sistêmico; Fatores críticos de sucesso; Fatores críticos de insucesso; Design science research; Strategy deployment; Systems thinking; Critical success factors; Critical failure factors; Design science research; ACCNPQ::Engenharias::Engenharia de Produção